Diversitas Dewan Direksi dan Pengaruhnya terhadap Kinerja Bank: Studi Empiris pada Perbankan di Indonesia - Jul Aidil Fadli; Tyasa Carolina (Universitas Agung Podomoro, 2021)
The importance of banking for the economy of a country and even the world, demands the skills of the board of directors in the banking industry who are qualified in managing companies and competing in changing economic situation. The diversity of gender, level of education and tenure in office will influence their interpretation of the situation at hand and influence their strategic decisions. This study will focus on the diversity of characteristics of the board of directors in terms of the presence of female directors in the structure of the board of directors, tenure, and education level of the board of directors and their influence on company outcomes which are conceptually reviewed based on previous studies.